Characterizing healthcare delivery in the United States using Census Bureau's County Business Patterns (2000–2016). (June 2020) - KC, Astha; Schaefer, Melissa K.; Stone, Nimalie D.; Perz, Joseph
Abstract: Background: The US Census Bureau's County Business Patterns (CBP) series provides a unique opportunity to describe the healthcare sector using a single, national data source. Methods: We analyzed CBP data on business establishments in the healthcare industry for 2000–2016 for all 50 states and the District of Columbia. Setting and facility types were defined using the North American Industry Classification System. Results: In 2016, CBP enumerated 707, 634 US healthcare establishments (a 34% increase from 2000); 86.5% were outpatient facilities and services followed by long-term care facilities (12.5%) and acute-care facilities (1.0%). Between 2000 and 2016, traditional facilities such as general medical surgical and surgical hospitals (−0.4%) and skilled nursing facilities (+0.1%) decreased or remained flat, while other long-term care and outpatient providers grew rapidly. Conclusion: This analysis highlights the steady growth and increased specialization of the US healthcare sector, particularly in long-term care and outpatient settings.